Protective Mechanisms of Quercetin Against Myocardial Ischemia Reperfusion Injury - Zhang, Yu-Min; Zhang, Zhen-Ye; Wang, Ru-Xing (Frontiers in Physiology, 2020)
Quercetin has attracted more attention in recent years due to its protective role against ischemia/reperfusion injury. Quercetin can alleviate oxidative stress injury through the inhibition of NADPH oxidase and xanthine oxidase, blockage of the Fenton reaction, and scavenging of reactive oxygen species. Quercetin can also exert anti-inflammatory and anti-apoptotic effects by reducing the response to inflammatory factors and inhibiting cell apoptosis. Moreover, it can induce vasodilation effects through the inhibition of endothelin-1 receptors, the enhancement of NO stimulation and the activation of the large-conductance calcium-activated potassium channels. Finally, Quercetin can also antagonize the calcium overload. These multifaceted activities of Quercetin make it a potential therapeutic alternative for the treatment of ischemia/reperfusion injury.